Three-dimensional organization of cell adhesion junctions at synapses and dendritic spines in area CA1 of the rat hippocampus - Spacek, J; Harris, K M (The Journal of comparative neurology, 1998)
Recent work has emphasized the role of adhesion molecules in synaptic plasticity, including long-term potentiation in the hippocampus. Such adhesion molecules are concentrated in junctions that are characterized by dense thickenings on both sides of the junction and are called puncta adhaerentia (PA). Reconstruction from serial electron microscopy was used to determine the location and size of PA in the stratum radiatum of hippocampal area CA1, where many of the previous functional studies have been performed. PAs were found at the edges of synapses on 33% of dendritic spines. The areas occupied by PA were variable across different types of synapses, occupying 0.010+/-0.005 microm2 at macular synapses and 0.034+/-0.031 microm2 at perforated synapses. Another zone, called a vesicle-free transition zone (VFTZ), was identified. Like the PA, this zone also had no presynaptic vesicles and was located at the edges of synapses; however, unlike the PA, the presynaptic thickening was less than the postsynaptic thickening. Together, 45% of spine synapses had PA and/or VFTZ occupying 23+/-11% of the total junctional area between axons and spines. PA also occurred at nonsynaptic sites involving neuronal as well as glial elements. Most (64%) of these PAs occurred between nonsynaptic portions of dendritic spines and neighboring astrocytic processes. Smooth endoplasmic reticulum was often apposed to one or both sides of the synaptic and the nonsynaptic PA. These findings provide further data as a structural basis for understanding the roles of cell adhesion junctions in hippocampal synaptic function and plasticity.
Keywords: synapse; Microscopy, Electron; dendrity; Intercellular Junctions; Rats, Inbred Strains; krysa rodu Rattus; Hippocampus; Cell Adhesion; Neuropil; zvířata; neurony; hipokampus; počítačové zpracování obrazu; Dendrites; Image Processing, Computer-Assisted; Male; hladké endoplazmatické retikulum; neuropil; Neurons; Endoplasmic Reticulum, Smooth; Rats; elektronová mikroskopie; buněčná adheze; Animals; mezibuněčné spoje; mužské pohlaví; Synapses; inbrední kmeny potkanů